Special Autonomy as Indonesia’s National Policy to Improve the Welfare of the People of Papua - M. Alfi Rajabi Nasution; Poltak Partogi Nainggolan (The Republic of Indonesia Defense University, 2023)
Indonesia has applied special autonomy to make Papua pursue other provinces' development progress and end the separatist movement for 22 years since 2001. The policy has not been successful because separatism, terrorism, and insurgency against Indonesia in various remote areas and urban areas of Papua Province causing fatalities from civilians, Papuan Native, Indonesian National Armed Forces/Police, and Papuan Terrorist Separatist Groups themselves continue to emerge, precisely when Papua should focus on implementing their special autonomy policy. This study discusses how the special autonomy had been implemented as a national policy to improve the welfare of the people of Papua amidst the increasing intensity of the separatism, terrorism, and insurgency carried out by the Papuan Terrorist Separatist Group. This study uses a qualitative method and a descriptive analysis approach; data was obtained by literature study and deep interview techniques with various stakeholders. This study reveals that the state budget allocated for the special autonomy was not used properly based on the good governance principle as previously expected by the central Government. In contrast, the money was found illegally transferred to the Papuan Terrorist Separatist Group, supporters (active and passive), and sympathizers to operate their armed struggles, separatism, and propaganda activities, undermining the authority of the central Government and threatening the sovereignty of Indonesia. This study recommends the special autonomy policy be prolonged and strengthened for the next two decades with conditionalities that it should be prepared with detailed development planning and transparent and good supervision involving various stakeholders. Furthermore, the division of the Province in Papua from the current two into five provinces must be accelerated to bring the national development present in the Papuan Natives.